Promising Strategies to Reduce the SARS-CoV-2 Amyloid Deposition in the Brain and Prevent COVID-19-Exacerbated Dementia and Alzheimer's Disease - Nikita Navolokin; Viktoria Adushkina; Daria Zlatogorskaya; Valeria Telnova; Arina Evsiukova; Elena Vodovozova; Anna Eroshova; Elina Dosadina; Sergey Diduk; Oxana Semyachkina-Glushkovskaya (MDPI AG, 2024)
The COVID-19 pandemic, caused by infection with the SARS-CoV-2 virus, is associated with cognitive impairment and Alzheimer's disease (AD) progression. Once it enters the brain, the SARS-CoV-2 virus stimulates accumulation of amyloids in the brain that are highly toxic to neural cells. These amyloids may trigger neurological symptoms in COVID-19. The meningeal lymphatic vessels (MLVs) play an important role in removal of toxins and mediate viral drainage from the brain. MLVs are considered a promising target to prevent COVID-19-exacerbated dementia. However, there are limited methods for augmentation of MLV function. This review highlights new discoveries in the field of COVID-19-mediated amyloid accumulation in the brain associated with the neurological symptoms and the development of promising strategies to stimulate clearance of amyloids from the brain through lymphatic and other pathways. These strategies are based on innovative methods of treating brain dysfunction induced by COVID-19 infection, including the use of photobiomodulation, plasmalogens, and medicinal herbs, which offer hope for addressing the challenges posed by the SARS-CoV-2 virus.